Pembangunan Modal Manusia: Kajian Terhadap Pulangan Negara-Negara Islam Terpilih - Sulaiman, A. A.; Shuib, M. S.; Mohamad, M. T. (Universiti Sains Islam Malaysia, 2024)
Human capital is important sources of input in order to move the economy in a country. Without Human capital intensive, productive and quality, a country can't use the economic resources to produce maximum output. Islamic countries are very popular with many natural resources. However these resources not fully use due to a number of shortcomings that exist, particularly involving the Human capital. In accordance with the above issues and problems. The objective of this study is to examine the Human capital development through education in Muslim countries in Asia could drive economic growth. The results showed the development of human capital through indicators of participation rates of students at primary, secondary, university and government spending on education is a factor affecting the leve1 of Gross Domestic Product (GDP) of Islamic countries in Asia.